2004
DOI: 10.1097/00000372-200410000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Differential Diagnosis of Keloid and Hypertrophic Scar

Abstract: Distinguishing hypertrophic scar (HS) from keloid histopathologically is sometimes difficult because thickened hyalinized collagen (keloidal collagen), the hallmark of keloid, is not always detectable and alpha-smooth muscle actin (alpha-SMA), a differentiating marker of HS, is variably expressed in both forms of scar. The aim of this study was to investigate additional distinguishing features to facilitate differentiation between keloid and HS. We compared various histologic features and the expression of alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
252
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(264 citation statements)
references
References 14 publications
8
252
1
3
Order By: Relevance
“…8 In addition to differences in clinical appearance, keloids often differ histopathologically from hypertrophic scars in a variety of ways, with the most distinguishing feature being the presence of thickened hyalinized collagen (keloidal collagen). 9 Keloid formation has also been associated with a family history of keloids, hyperimmunoglobulin E syndrome, blood type A, and hormone peaks during puberty and pregnancy. [10][11][12][13] …”
Section: Scar Morphologymentioning
confidence: 99%
“…8 In addition to differences in clinical appearance, keloids often differ histopathologically from hypertrophic scars in a variety of ways, with the most distinguishing feature being the presence of thickened hyalinized collagen (keloidal collagen). 9 Keloid formation has also been associated with a family history of keloids, hyperimmunoglobulin E syndrome, blood type A, and hormone peaks during puberty and pregnancy. [10][11][12][13] …”
Section: Scar Morphologymentioning
confidence: 99%
“…The sine qua non of keloids is the growth of the lesion beyond original wound margins (2)(3)(4). Keloids consist of a quiescent central area surrounded by an active leading edge that is frequently erythematous and pruritic (1).…”
Section: Introductionmentioning
confidence: 99%
“…Keloids consist of a quiescent central area surrounded by an active leading edge that is frequently erythematous and pruritic (1). Histologically, keloids are seen to invade adjacent reticular dermis beneath normal-appearing papillary dermis and epidermis (2). Previous research has demonstrated that keloid fibroblasts proliferate and migrate more rapidly than control dermal fibroblasts (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…A hallmark of myofi broblasts is the expression of α-SMA. 18,19 Therefore, α-SMA may be a marker for fi brosis and scar formation. We analyzed α-SMA expression by immunohistochemistry at day 14 after injury and found that deposition of α-SMA in the eccentric exercise group was more subdued than that in the concentric exercise group.…”
mentioning
confidence: 99%